Economic Effects of Inward Foreign Direct Investment: The Case of Vietnamese Provinces - TAGUCHI, Hiroyuki; PHAM, Huyen Khanh (Journal of Advanced Studies in Finance; Vol 10 No 1 (2019): JASF Volume X Issue 1(19) Summer 2019DO - 10.14505//jasf.v10.1(19).02, 2019)
This article examines the effect of foreign direct investment (FDI) on economic growth and domestic investment with a focus on Vietnamese provinces by conducting a vector auto-regression (VAR) estimation. The major research questions are twofold: whether the inward FDI causes economic growth or economic growth induces the FDI, and whether the inward FDI crowds in or crowds out domestic investment. This study explores regional differences in the FDI effect by dividing Vietnamese provinces according to FDI-value intensity. The VAR estimation results showed two clear contrasts on FDI effects between the FDI-intensive region and the FDI-less-intensive one. One contrast was that FDI causes economic growth in the FDI-intensive region, whereas economic growth induces FDI in the FDI-less-intensive region. Another contrast was that FDI crowds in domestic investment in the FDI-intensive region, whereas FDI crowds out domestic investment in the FDI-less-intensive region. These contrasts suggest the existence of FDI’s agglomeration effects.